1979
DOI: 10.1063/1.90647
|View full text |Cite
|
Sign up to set email alerts
|

Increase in luminescence efficiency of AlxGa1−xAs grown by organometallic VPE

Abstract: A modification of the cold-wall organometallic vapor-phase epitaxial (OMVPE) process for the growth of AlxGa1−xAs layers is described. Graphite baffles placed in the gas stream act to greatly increase the photoluminescence efficiency of the AlxGa1−xAs. Preliminary evidence indicates that the effect of the baffles may be to provide a solid surface upon which Al2O3 can be deposited from the reaction of trimethylaluminum with any residual O2 and/or H2O in the vapor phase. The ’’gettering’’ action apparently reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In MBE Al,Gal-,As alloys, the carbon content is always high, in the 10'' cm-3 range (D M Collins 1981 private communication). For most devices, the low roomtemperature electron mobilities due to scattering by C in A1,Gal-,As are not Chandra and Eastman (1980); A LPE, Stringfellow (1979a,b); 0, OMVPE, Stringfellow (1979); W Ge-doped MBE GaAs, Stringfellow (1980b); + Zn-doped VPE GaAs, Bruch et a1 (1979); 0 Ge-doped LPE GaAs, Stringfellow (1980b).…”
Section: Organometallic Vpementioning
confidence: 99%
“…In MBE Al,Gal-,As alloys, the carbon content is always high, in the 10'' cm-3 range (D M Collins 1981 private communication). For most devices, the low roomtemperature electron mobilities due to scattering by C in A1,Gal-,As are not Chandra and Eastman (1980); A LPE, Stringfellow (1979a,b); 0, OMVPE, Stringfellow (1979); W Ge-doped MBE GaAs, Stringfellow (1980b); + Zn-doped VPE GaAs, Bruch et a1 (1979); 0 Ge-doped LPE GaAs, Stringfellow (1980b).…”
Section: Organometallic Vpementioning
confidence: 99%
“…The initial studies of MOVPE Al x Ga 1Ϫx As have often reported materials that exhibited a low photoluminescence ͑PL͒ efficiency and a reduced free electron concentration, when co-doped with shallow donors. 1,2 Both observations have been attributed to the incorporation of oxygen that results in deep level centers. These defects or defect complexes are effective nonradiative recombination centers, reducing the PL efficiency, and can compensate the shallow donors.…”
Section: Introductionmentioning
confidence: 99%